El software LMS y su relación con la enseñanza remota en alumnos de segunda especialidad profesional, 2022 - Caballero Núñez, Angela Luz (2023)
This study examines the relationship between LMS (Learning Management System) software and remote teaching in the Second Professional Specialization Program (PSEP) at the Faculty of Education Sciences (FCED) of the National University of Huancavelica (UNH) during the academic year 2022. The hypothesis posits that the implementation of LMS software significantly enhances remote teaching in this program. Using a quantitative, explanatory approach and an experimental-correlational design, a sample of 211 participants was selected from a population of 935. Two online questionnaires were administered to collect and analyze the data. The statistical results confirm the hypothesis with a significance level of α = 0.05 and a correlation of r=0.763, demonstrating a considerable positive correlation between LMS software and remote teaching. These findings highlight the importance of LMS software in remote teaching, particularly in the PSEP-FCED program at UNH. The identified positive correlation shows how the implementation of LMS tools improves the learning experience and teaching effectiveness in remote environments. These results contribute to the knowledge on educational technology and provide practical insights for enhancing remote teaching practices in educational institutions.